2022
DOI: 10.3390/s22041690
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Simplified Inertial Sensor Method against Electrogoniometer for Measuring Wrist Motion in Occupational Studies

Abstract: Wrist velocity is an important risk factor for work-related musculoskeletal disorders in the elbow/hand, which is also difficult to assess by observation or self-reports. This study aimed to evaluate a new convenient and low-cost inertial measurement unit (IMU)-based method using gyroscope signals against an electrogoniometer for measuring wrist flexion velocity. Twelve participants performed standard wrist movements and simulated work tasks while equipped with both systems. Two computational algorithms for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…With today’s developments, there are easy-to-use technical methods for research and field studies. In the future, the use of such methods [ 43 ], together with scientifically based action levels [ 44 ], should be considered. The current finding of worker gender-related differences in estimates is another reason to consider the use of objective methods.…”
Section: Discussionmentioning
confidence: 99%
“…With today’s developments, there are easy-to-use technical methods for research and field studies. In the future, the use of such methods [ 43 ], together with scientifically based action levels [ 44 ], should be considered. The current finding of worker gender-related differences in estimates is another reason to consider the use of objective methods.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 3, IMUs are increasingly being used for kinematic measurements of the arms and trunk [69,116], while twin-axis goniometers (electrogoniometers) still seem to dominate kinematics measurements of the wrist [46,117].…”
Section: Ambulatory Motion Capture Instruments and Systemsmentioning
confidence: 99%
“…The generalizability of such conversion equations to multiple occupational groups is yet to be tested; hence, more research is needed. As shown in Table 3, IMUs are increasingly being used for kinematic measurements of the arms and trunk [69,116], while twin-axis goniometers (electrogoniometers) still seem to dominate kinematics measurements of the wrist [46,117].…”
Section: Ambulatory Motion Capture Instruments and Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peppoloni et al successfully demonstrated such a system, however, the use of EMG further compounds the procedural difficulty of usage in the workplace [ 18 ]. While challenges exist in the direct measurement of wrist kinematics with IMUs, one alternative is to assess metrics other than joint angle such as joint angular velocity, which can be directly measured using gyroscopes placed across the joint as demonstrated by Manivasagam and Yang [ 19 ]. This approach offers a much more practical approach to extracting data, however, from a practical standpoint it is still very much the domain of research.…”
Section: Introductionmentioning
confidence: 99%